Subject Review on Some Analytical Methods for Determination of Fosfomycin Drugs - Khalil, Ali; Al-Janabi, Khalid Waleed S.; Dheyab Sallal, Takleef (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2022)
Medicines comprising fosfomycin are prescribed for urinary tract infections. These drugs are available for oral use as tromethamine and calcium, while fosfomycin-sodium and disodium are given for intravenous (IV) and intramuscular (IM). Many quantitative analytical methods have been reported to estimate Fosfomycin in blood, urine, plasma, serum, and pharmaceutical dosage formulations. Some techniques were spectrophotometric, mass spectrometry, gas chromatography, high-performance liquid chromatography, and electrochemical methods. Here we perform a rapid narrative review that discusses and comparison between them of various analytical methods for the determination of Fosfomycin-containing drugs.